THEORETICAL BASIS OF IMPROVING THE STRUCTURAL STRUCTURE OF INDUSTRIAL INDUSTRIES (Scientific electronic journal "Labor Economics and Human Capital", 2025)
Achieving the strategic goals of national economic development implies a step-by-step transition from the agrarian-industrial model of development to the industrial-agrarian model, taking into account the comprehensive use of the potential of industrial sectors based on the wide introduction of innovative technologies. competitiveness of the country's economy. In the modern world, the formation of industrial potential and its effective use serve as the main factor of ensuring economic security. At the same time, "...domestic policy should be focused on reducing the vulnerability of the country's economy to potential external threats, searching for and developing effective mechanisms and internal sources of sustainable economic development, ensuring sustainable economic growth, effective employment, and sustainable use.
Keywords: industry, capital, labor, goods market (IS), money market (LM), balance of payments, interest rate, return on capital, technology, capital accumulation, savings rate.